The Impact of the Energy Conservation Law on Enterprise Energy Efficiency: Quasi-Experimental Evidence from Chinese Firms - Hongwei Yu; Wenjin Chen; Xinyi Wang; Laurence Delina; Zhiming Cheng; Le Zhang (Global Labor Organization (GLO), 2023)
We employ a regression discontinuity design (RDD) to investigate the causal effect of China's Energy Conservation Law (ECL) on the energy efficiency of Chinese firms. Using data from the 2018 China Employer-Employee Survey (CEES), we find that the energy regulation has a positive impact on enterprise energy efficiency. Furthermore, we observe that the effects of the regulation vary across industries, ownership types, and firm ages. We also find that energy management system (EnMS) and technological innovation are mechanisms through which the energy regulation helps improve enterprise energy efficiency. These findings underscore the importance of well-designed and effectively implemented energy regulations in fostering energy efficiency and reducing carbon emissions in the industrial sector. They also highlight the need to consider the heterogeneity of the regulatory impact when designing energy-saving policies.
Keywords: K32; Q56; Q58; 330; Energy Conservation Law; energy regulation; energy efficiency; China; regression discontinuity design